Assessment of the clinical profile in the children with microcephaly: Random sampling study - Dr. Gaurang Dilipkumar Pabani; Dr. Rajeshri Rajendra Mehta; Dr. Pramod Chandulal Shah (Pediatric Review: International Journal of Pediatric Research, 2020)
Background and Aim: Primary Microcephaly is also associated with at least 7 gene loci, and 7 single etiologic genes have been identified. Acquired microcephaly can be seen in conditions such as rett, seckel, and angel syndromes and encephalopathy syndrome associated with severe seizure disorders. Hence the study was done to assess the clinical profile of microcephaly in children. Materials and Methods: A total of 104 children were included in the study. The children were divided into different groups as per age distribution. Group A consist of children of age less than 1 year, in group B there were children between age 1 – 5 years, in group C the age of children included was 5 to 10 years and in group D the age of children was more than 10 years. Results: There were 30 children with microcephaly in group A, in group B there were 52 children with microcephaly. For group C there were 20 children with microcephaly and for group D there were 2 children with microcephaly. The maximum numbers of children were in the age group of 1 to 5 years. Conclusion: Microcephaly is a frequent clinical sign which is common in many of the rare diseases, henceforth, as the exact diagnosis is important for counseling the patient and the affected family, regarding the clinical course, possible complication, optimized medical support, and recurrent risk.